An Integrative Model of Organizational Communication and Values-Based Work Culture for Enhancing Employee Engagement and Organizational Performance in a Catholic Higher Education Institution - Lestari Pratiwi Sitanggang; Miska Irani Br Tarigan; Donalson Silalahi; Pandapaotan Sitompul (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
The transformation of higher education governance requires universities to develop management systems that not only focus on organizational performance but also foster employee engagement through effective organizational communication and a values-based work culture. This study aims to develop and empirically test an integrative model examining the effects of organizational communication and values-based work culture on organizational performance through employee engagement at Universitas Katolik Santo Thomas. A quantitative explanatory research design was employed. Data were collected from 150 respondents, comprising permanent academic staff and administrative personnel, selected using purposive sampling. The data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings indicate that organizational communication does not have a significant effect on employee engagement but has a positive and significant direct effect on organizational performance. In contrast, a values-based work culture has positive and significant effects on both employee engagement and organizational performance. Furthermore, employee engagement positively influences organizational performance and partially mediates the relationship between values-based work culture and organizational performance, while it does not mediate the relationship between organizational communication and organizational performance. The proposed model explains 55.6% of the variance in organizational performance. This study proposes an integrative model that links structural, values-based cultural, and psychological dimensions in enhancing organizational performance within a values-based higher education institution. The findings extend Social Exchange Theory and contribute to the growing body of knowledge on organizational management in values-based higher education institutions.